The demise of the interest and its impact on the proceeding in the annulment lawsuit - a comparative study - خليل إبراهيم, مدرس دكتور يوسف (The college of law and political science journal, 2023)
7KHH[LVWHQFHRIDQLQWHUHVWLVDEDVLFDQGLPSRUWDQWFRQGLWLRQIRUÀOLQJDODZVXLWto annul the administrative decision, but this interest may disappear and expireGXULQJWKH FRQVLGHUDWLRQ RIWKH DQQXOPHQW ODZVXLW DQG EHIRUHWKH ÀQDO GHFLVLRQon it. In this case, the Egyptian and Iraqi administrative judiciary have settled toconsider that the litigation ended with the demise of the appellant’s interest, incontrast to what was settled by the French administrative judiciary, and throughour research, we want to shed light on the need to continue and proceed with thelawsuit to cancel the contested administrative decision despite the demise andexpiration of the contested administrative decision. the personal interest of theSHUVRQÀOLQJWKHDQQXOPHQWDFWLRQDVHVWDEOLVKHGE\WKH)UHQFK&RXQFLORI6WDWHThis is to ensure the protection of the principle of the legality of the administrativedecision and the achievement of the public interest